High frequency impedance based fault location in distribution system with DGs - Jia, Ke; Bi, Tianshu; Ren, Zhefeng; Thomas, David W.P.; Sumner, M. (Institute of Electrical and Electronics Engineers, 2018)
Distributed Generations (DGs) with power electronic devices and their control loops will cause distortion to the fault currents and result in errors for power frequency measurement based fault locations. This might jeopardize the distribution system fault restoration and reduce the grid resilience. The proposed method uses high frequency (up to 3kHz) fault information and short window measurement to avoid the influence of DG control loops. Applying the DG high frequency impedance model, faults can be accurately located by measuring the system high frequency line reactance. Assisted with the DG side recorded unsynchronized data, this method can be employed to distribution systems with multiple branches and laterals. 